Validation of maximal, submaximal, and nonexercise indirect VO2max estimations at 2600 m altitude - Duperly, J.; Serrato, M.; Forero, N. I.; Jimenez-Mora, M. A.; Mendivil, C. O.; Lobelo, F. (High Altitude Medicine & Biology, 2020)
Aim: To study the criterion validity of three indirect maximal oxygen uptake (O2max) assessment equations at altitude.